Amplitude modulated Bloch oscillations of photon probability distribution in a cavity–atom system. (17th March 2015) - Zhang, G; Hu, WH; Song, Z
Abstract: We study the dynamics of the Rabi Hamiltonian in the medium coupling regime with, where g is the atom-field coupling constant and ω is the field frequency, for the quantum state with average photon number . We map the original Hamiltonian to an effective one, which describes a tight-binding chain subjected to a staggered linear potential. It is shown that the photon probability distribution of a Gaussian-type state exhibits amplitude-modulated Bloch oscillations (BOs), which are a superposition of two conventional BOs with a half-BO-period delay between them and are essentially another type of Bloch–Zener oscillation. The probability transition between the two BOs can be controlled and suppressed by the ratio, as well as the in-phase resonant oscillating atomic frequency Ω ( t ), leading to multiple zero-transition points.